2006
DOI: 10.2353/ajpath.2006.050332
|View full text |Cite
|
Sign up to set email alerts
|

A Tumor Necrosis Factor Receptor 1-Dependent Conversation between Central Nervous System-Specific T Cells and the Central Nervous System Is Required for Inflammatory Infiltration of the Spinal Cord

Abstract: Experimental autoimmune encephalomyelitis (EAE) is an autoimmune demyelinating disease of the central nervous system (CNS). Because of similarities in clinical symptoms and CNS histology, 1-5 EAE serves as a model for multiple sclerosis and can be induced in mice by either immunization with myelin protein or peptides 6 or by adoptive transfer of myelin-specific Th1 CD4 ϩ T cells. 7,8As a result, inflammatory cells consisting mostly of CD4 ϩ T lymphocytes and macrophages infiltrate the CNS leading to demyelinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…TNF␣ signaling via TNFR1 plays a dominant role in mediat- ing inflammation in numerous diseases (Probert et al, 2000;Gimenez et al, 2006). To determine whether differential TNF␣ signaling via TNFR1 or TNFR2 affects cerebral monocyte recruitment in BDR mice, we conducted recruitment studies in day 10 BDR mice deficient in TNFR1 or TNFR2.…”
Section: Discussionmentioning
confidence: 99%
“…TNF␣ signaling via TNFR1 plays a dominant role in mediat- ing inflammation in numerous diseases (Probert et al, 2000;Gimenez et al, 2006). To determine whether differential TNF␣ signaling via TNFR1 or TNFR2 affects cerebral monocyte recruitment in BDR mice, we conducted recruitment studies in day 10 BDR mice deficient in TNFR1 or TNFR2.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data suggest that astrocyte interactions with the cerebrovasculature endothelium play a key role in the induction and maintenance of the tight junctions characteristic of the intact BBB. Furthermore, astrocyte production of pro-inflammatory cytokines such as TNFα play key roles in facilitating leukocyte extravasation from the bloodstream across the BBB into the CNS parenchyma [29][30][31][32]. Lastly, it is largely unexplored to what extent the many homeostatic functions of astrocytes such as the buffering of pH and glutamate are significantly altered by their cellular transition into "reactive" astrocytes.…”
Section: Why Focus On Astrogliosis When Discussing Neuroinflammation?mentioning
confidence: 99%
“…Akassoglou et al (1998) demonstrated a dominant role for TNFR1 signaling in TNF-mediated oligodendrocyte apoptosis and primary demyelination [147]. In addition, TNFR1 was suggested to contribute to inflammatory infiltration of the EAE spinal cord [148]. Interestingly, it was recently shown in different studies that administration of an antagonistic antibody that selectively targets TNFR1 ameliorated disease symptoms in the EAE mouse model [18,149].…”
Section: Multiple Sclerosismentioning
confidence: 99%